2022
DOI: 10.3390/biomedicines10102489
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Sustains Pancreatic Cancer Cell Survival and mutp53 Stability through the Mevalonate Pathway

Abstract: It has been shown that wild-type (wt)p53 inhibits oncogene c-Myc while mutant (mut)p53 may transactivate it, with an opposite behavior that frequently occurs in the crosstalk of wt or mutp53 with molecules/pathways promoting carcinogenesis. Even if it has been reported that mutp53 sustains c-Myc, whether c-Myc could in turn influence mutp53 expression remains to be investigated. In this study, we found that pharmacological or genetic inhibition of c-Myc downregulated mutp53, impaired cell survival and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This mechanism can be disrupted by statins, cholesterol-lowering drugs, that, by reducing the level of mevalonate-5-phosphate in the mevalonate pathway (MVP), induce CHIP-mediated degradation of mutp53 [87]. Accordingly, c-Myc inhibition has been shown to reduce the expression of mevalonate kinase (MVK), a molecule belonging to the mevalonate pathway, and reduce mutp53 stability [88]. heat shock proteins HSP90 and HSP70, along with HSP40, stabilize mutp53, preventing its ubiquitination and degradation.…”
Section: Mutant P53 Degradation: the Proteasomal Routementioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism can be disrupted by statins, cholesterol-lowering drugs, that, by reducing the level of mevalonate-5-phosphate in the mevalonate pathway (MVP), induce CHIP-mediated degradation of mutp53 [87]. Accordingly, c-Myc inhibition has been shown to reduce the expression of mevalonate kinase (MVK), a molecule belonging to the mevalonate pathway, and reduce mutp53 stability [88]. heat shock proteins HSP90 and HSP70, along with HSP40, stabilize mutp53, preventing its ubiquitination and degradation.…”
Section: Mutant P53 Degradation: the Proteasomal Routementioning
confidence: 99%
“…Given the complex pattern of PTMs and the importance that they play in regulating HSP functions, the term "chaperone code" Regarding the small HSP27, whose hyperexpression and role in cancer cell survival has been largely demonstrated [142], it is known to interact with wtp53 [143] but if it could regulate mutp53 expression is not completely clarified, although its overexpression seems to deplete mutp53 rather than stabilizing it [144]. In a recent study it was shown that, although downregulated by a c-Myc inhibitor, HSP27 did not contribute to the reduction of mutp53 expression level induced by such a treatment [88]. Even less known is the role of HSP110 in the regulation of mutp53 stability, also because no specific inhibitors for this HSP are yet commercially available.…”
Section: Targeting Hsp Expression and Posttranslational Modifications...mentioning
confidence: 99%
“…KRAS is known to stabilize CMYC by activating the ERK1/2 which phosphorylates CMYC at serine 62 11 . Several studies demonstrated that mutant p53 and MYC may positively influence each other’s levels and activity 12, 13 . Furthermore, transcriptional signature of mutant p53 in head and neck squamous cell carcinoma was enriched in MYC targets, and mutant p53 augmented CMYC binding to its target promoters 14 .…”
Section: Introductionmentioning
confidence: 99%